Line-Field Confocal Optical Coherence Tomography Evaluation of Eyelid Skin Lesions - Di Stefani, Alessandro; Cappilli, Simone; Cuffaro, Giovanni; Fionda, Bruno; Pagliara, Monica Maria; Paradisi, Andrea; Ricci, Costantino; Rossi, Ernesto; Sammarco, Maria Grazia; Schinzari, Giovanni; Tagliaferri, Luca; Blasi, Maria Antonietta; et al. (Diagnostics (Basel), 2023)
Background: Periocular malignancies may be clinically different from the examples arising at other sites, with possible delayed diagnosis and greater challenges for treatment and repair. Line-field confocal optical coherence tomography (LC-OCT) is a recently developed technique characterized by an unprecedented capacity to acquire high-definition images in vertical and horizontal modes. In this study, we aimed to investigate the LC-OCT morphological features of a series of eyelid skin lesions, correlating them to histopathological findings. Methods: Patients with biopsy-proven equivocal skin lesion in the eyelid area, previously investigated by means of LC-OCT, were included in the study. Percentage overall agreement was estimated for LC-OCT and histopathological diagnosis for study cases. Results: A total of 51 patients (28 women, 23 men; mean age 66.4 years old), for a total of 51 skin lesions, were assessed. The histopathological diagnosis consisted of 30 malignant and 21 benign tumors. Different entities were characterized by peculiar findings in LC-OCT, alike to histopathological features, allowing for an accurate “in vivo” classification in almost all cases, with a diagnostic concordance with histopathology of 92.1% (47/51). Conclusions: By integrating this new imaging technique into the assessment of suspicious tumors in this area, diagnostic accuracy may increase, improving strategies adopted in multidisciplinary meetings and patient-centered care.